1997
DOI: 10.1021/jp972718f
|View full text |Cite
|
Sign up to set email alerts
|

Water Confined in Reverse Micelles:  Acoustic and Densimetric Studies

Abstract: We have used a custom-built ultrasound velocimeter to carry out high-precision velocity measurements of reverse micelle solutions, made of ionic (AOT) and nonionic (C12E4) surfactants in oil, as a function of water concentration. We show that the observed velocity variation as a function of increasing water concentration differs from the characteristics of the surfactant polar headgroups. The complex profile of compressibility curves obtained from velocity and densimetric measurements can be accounted for by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 29 publications
6
48
0
1
Order By: Relevance
“…1 H NMR experiments indicated that the reverse micelles contained a pool of free water, even at a Wo ϭ 3.75. Several other approaches, such as time-resolved fluorescence Stokes shift and analysis of the compressibility of water in reverse micelles also found free water in C 12 E 4 /TMP micelles at Wo from 1.1 to 5 (Caldararu et al, 1994;Amararene et al, 1997;Waysbort et al, 1997;Pant and Levinger, 2000). Thus, both the CD spectra and NMR determination of free water content indicate that the DNA in neutral reverse micelles is not condensed simply from dehydration.…”
Section: Discussionmentioning
confidence: 88%
“…1 H NMR experiments indicated that the reverse micelles contained a pool of free water, even at a Wo ϭ 3.75. Several other approaches, such as time-resolved fluorescence Stokes shift and analysis of the compressibility of water in reverse micelles also found free water in C 12 E 4 /TMP micelles at Wo from 1.1 to 5 (Caldararu et al, 1994;Amararene et al, 1997;Waysbort et al, 1997;Pant and Levinger, 2000). Thus, both the CD spectra and NMR determination of free water content indicate that the DNA in neutral reverse micelles is not condensed simply from dehydration.…”
Section: Discussionmentioning
confidence: 88%
“…in the form of water clusters around the above groups; (iii) free state that admits the presence of water as a separate phase. According to [21], each AOT molecule can rigidly bind 2-3 water molecules and about 13 trapped water molecules. Meanwhile, the fluorescence measurements for 8-anilino-1-naphthalenesulfonic acid in AOT RMs [22] clearly indicated that, at fixed W , the amount of free water grew with increasing n. This was associated with a change in the packing density of surfactant molecules in the micellar shell.…”
Section: Factors Responsible For the Growth Of Nanoparticlesmentioning
confidence: 99%
“…A peak at $400 nm indicates the selective excitation of the probe molecules residing at the interface. 10), the properties of the confined water differ from those of the bulk water [171][172][173]. (b) Emission spectrum of C-500 at different temperatures for AOT/i-Oc reverse micelles with w 0 ¼ 5.…”
Section: Resultsmentioning
confidence: 99%